Prevalensi Infeksi Cacing Pita Pada Ayam Petelur (Gallus gallus) Di Peternakan Ayam Petelur Timor Raya Oesao, Kecamatan Kupang Timur, Kabupaten Kupang - Bude, Plasedis Olgaviana; Almet, Julianty; Winarso, Aji (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
Tapeworm is one of the endoparasites that often infect laying hens so that it will cause economic losses for farmers because it can result in decreased egg production, body weight and growth disorders. This study aims to identify and calculate the prevalence of tapeworms in laying hens in the Laying Chicken Farm of Timor Raya Oesao, East Kupang District, Kupang Regency. The sample used in this study was 99 laying hens feces and examined using a simple flotation method. The sample is then observed under a microscope to identify the type of tapeworm eggs that infect laying hens. The results of the calculation show that the prevalence of tapeworm infection that occurs in laying hens at the Laying Chicken Farm of Timor Raya Oesao, East Kupang District, Kupang Regency, of 99 samples, there were 14 samples that were positive for tapeworm eggs, namely Raillietina sp. with a prevalence rate of 11.1% and Hymenolepis sp. with a prevalence rate of 3.03%.